The use of high and low power lasers in the treatment of mucocele in lip: a case report - Neto, José Assis Cabral; Fernandes, Tiago Virgínio; Gomes, Daliana Queiroga de Castro; Filho, Tiago João; Pereira, Jozinete Vieira (Revista Estomatológica Herediana, 2022)
Mucocele is an inflammatory lesion of the common salivary gland in the oral cavity, generated by the accumulation of saliva, from the rupture of the minor salivary gland duct. The objective of this report was to describe a case of extravasation phenomena treated with high-power diode laser in association with photobiomodulation. The patient presented a nodular, exophytic lesion on the lower lip, similar in color to the mucosa, measuring 2 cm in diameter. Excisional biopsy was performed with high-power diode laser. Immediately after surgery and weekly thereafter, photobiomulation was performed with lower-power diode. After one-month, total repair of the surgical wound was observed, with minimal scarring, without lesion recurrence during 14 months of follow-up. Therefore, the treatment protocol used proved to be an effective, safe and fast alternative, bringing greater comfort to both professional and patient during the trans and postoperative periods.